Reactive oxygen species and nitric oxide scavenging nanoparticles alleviating rheumatoid arthritis through adjusting the seeds and growing soils - Peng Hua; Ruifeng Liang; Yanbei Tu; Yuying Yin; Man-Kay Law; Meiwan Chen (Elsevier, 2023)
Normalizing inﬂamed soils including reactive oxygen species (ROS), nitric oxide (NO), cell-free DNA, and regulating inﬂammation-related seeds such as macrophages, neutrophils, fibroblasts, represent a promising strategy to maintain synovial tissue homeostasis for rheumatoid arthritis (RA) treatment. Herein, ROS scavenging amphiphilic block copolymer PEGylated bilirubin and NO-scavenging PEGylated o-phenylenediamine were fabricated to self-assemble into a dually responsive nanoparticle loaded with JAK inhibitor notopterol (Not@BR/oPDA-PEG, NBOP NPs). The simultaneous ROS and NO depletion combined with JAK-STAT pathway inhibition could not only promote M2 polarization to reduce further ROS and NO generation, but also decrease cytokines and chemokines to prevent immune cell recruitment. Specifically, NBOP NPs responded to high level ROS and NO, and disintegrated to release notopterol in inﬂamed joints as the hydrophobic heads BR and oPDA were transformed into hydrophilic ones. The released notopterol could inhibit the JAK-STAT pathway of inflammatory cells to reduce the secretion of pro-inflammatory cytokines and chemokines. This strategy represented an effective way to regulate RA soils and seeds through breaking the positive feedback loop of inflammation aggravation, achieving an excellent anti-RA efficacy in a collagen-induced arthritis rat model. Taken together, our work offered a reference to adjust RA soils and seeds for enhanced RA treatment.